2008
DOI: 10.1016/j.juro.2008.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Dismembered Pyeloplasty: A 6-Year, Multi-Institutional Experience

Abstract: To our knowledge this review represents the largest multi-institutional experience of robotic dismembered pyeloplasty with long-term followup. Robotic pyeloplasty appears to be safe, durable and efficacious for primary and secondary ureteropelvic junction obstruction with or without concomitant stone extraction, and for patients with a solitary kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
2
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 19 publications
7
100
2
19
Order By: Relevance
“…Data favouring the robotic technique is now available from several other groups, confirming it to be safe, durable and effective [9,18]. It has also proved successful for secondary PUJO and concomitant stone extraction [18,19], and has been shown to be a superior minimally invasive option for managing PUJO [15]. Ours is a large single-centre experience of prospectively included consecutive cases from a tertiary-care centre.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Data favouring the robotic technique is now available from several other groups, confirming it to be safe, durable and effective [9,18]. It has also proved successful for secondary PUJO and concomitant stone extraction [18,19], and has been shown to be a superior minimally invasive option for managing PUJO [15]. Ours is a large single-centre experience of prospectively included consecutive cases from a tertiary-care centre.…”
Section: Discussionmentioning
confidence: 82%
“…Schwentner et al [8] reported a largest single-centre experience of 92 patients with a follow-up of 39 months with 96.7% success rate with 80 primary repairs and 12 secondary repairs. Data favouring the robotic technique is now available from several other groups, confirming it to be safe, durable and effective [9,18]. It has also proved successful for secondary PUJO and concomitant stone extraction [18,19], and has been shown to be a superior minimally invasive option for managing PUJO [15].…”
Section: Discussionmentioning
confidence: 95%
“…25 The steep learning curve for laparoscopic pyeloplasty may be smoothed by the adoption of robotic-assisted pyeloplasty, which appears to be as effective as open and laparoscopic approaches. [33][34][35][36] Other exciting developments, such as single-port pyeloplasty, are on the horizon. 37 In the meantime, laparoscopic pyeloplasty will remain the far superior treatment option for virtually all patients undergoing treatment of ureteropelvic junction obstruction.…”
Section: Resultsmentioning
confidence: 99%
“…3,7,[20][21][22][23][24] Splenic and hepatic lacerations can occur when robotic instruments are exchanged Postoperatively, the patient is carefully monitored for urine leakage, which may occur in less than 2% of cases. [20][21][22][23] Perioperative complications have occurred in 3% to 11% of cases. [20][21][22][23] If a urine leak occurs shortly after the procedure (within 1-2 h), abdominal radiography can confirm the position of the ureteral stent.…”
Section: Complicationsmentioning
confidence: 99%
“…[20][21][22][23] Perioperative complications have occurred in 3% to 11% of cases. [20][21][22][23] If a urine leak occurs shortly after the procedure (within 1-2 h), abdominal radiography can confirm the position of the ureteral stent. Distal migration of the stent up the ureter may necessitate ureteroscopy and basket retrieval of the distal end.…”
Section: Complicationsmentioning
confidence: 99%